2014
DOI: 10.1007/s00775-014-1144-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the atypical 5′-CG DNA sequence specificity of 9-aminoacridine carboxamide Pt complexes

Abstract: In this study, the DNA sequence specificity of four DNA-targeted 9-aminoacridine carboxamide Pt complexes was compared with cisplatin, using two specially constructed plasmid templates. One plasmid contained 5'-CG and 5'-GA insert sequences while the other plasmid contained a G-rich transferrin receptor gene promoter insert sequence. The damage profiles of each compound on the different DNA templates were quantified via a polymerase stop assay with fluorescently labelled primers and capillary electrophoresis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The damage profiles of the two DACP isomers (and to a lesser extent cisplatin) exhibit a preference to bind the first three telomeric repeats in the T7/ PvuII sequence, resulting in higher DNA damage intensities detected at the T2, T3 and T4 sites. It was intuitively thought that this bias towards the first cluster of telomeric repeats was due to excessive adduct formation inhibiting the Taq polymerase, which has previously been demonstrated for successively higher doses of cisplatin [12, 42]. However, it has been postulated that this may be because the 3′ end of the telomeric DNA repeats have an unusual conformation that exhibit an enhanced nucleophilicity [13].…”
Section: Discussionmentioning
confidence: 99%
“…The damage profiles of the two DACP isomers (and to a lesser extent cisplatin) exhibit a preference to bind the first three telomeric repeats in the T7/ PvuII sequence, resulting in higher DNA damage intensities detected at the T2, T3 and T4 sites. It was intuitively thought that this bias towards the first cluster of telomeric repeats was due to excessive adduct formation inhibiting the Taq polymerase, which has previously been demonstrated for successively higher doses of cisplatin [12, 42]. However, it has been postulated that this may be because the 3′ end of the telomeric DNA repeats have an unusual conformation that exhibit an enhanced nucleophilicity [13].…”
Section: Discussionmentioning
confidence: 99%
“…Two different clones, T7G10CpG and the HMHVR clone were made by modifying a pUC19 plasmid, using a previously described process. 19,20 These clones were used to determine the sequences at which the platinum conjugates bind.…”
Section: Dna Damage Studiesmentioning
confidence: 99%
“…The 9-aminoacridine intercalating group had a preference for 5'-CG dinucleotides and directed Pt binding to neighbouring G nucleotides. 19…”
Section: Selectivity Of Bindingmentioning
confidence: 99%
“…[27a] PT‐ACRAMTU (Figure ) has exhibited promising anticancer results against leukemia and ovarian cancer cell lines and has been demonstrated to be superior to cisplatin. [27b] Several other studies have shown that acridine‐containing metallointercalators exhibit enhanced cytotoxicity by a unified dual action involving increased DNA affinity, which is driven by the acridine's intercalating ability, and subsequent DNA damage by the vicinal metal through metal‐DNA base pair adduct formation …”
Section: Introductionmentioning
confidence: 99%
“…While examples of Pt, Au and Fe complexes conjugated to acridine moieties are known, there remains an opportunity to explore the chemical and anticancer properties of other metal complexes conjugated to acridine. Herein, we report the synthesis and characterization of a series of new 6,9‐dichloro‐2‐methoxyacridine‐containing ruthenium(II), osmium(II), rhodium(III) and iridium(III) half‐sandwich and ferrocenyl complexes.…”
Section: Introductionmentioning
confidence: 99%